2021
DOI: 10.1038/s41598-021-91286-0
|View full text |Cite
|
Sign up to set email alerts
|

Automated scoring of pre-REM sleep in mice with deep learning

Abstract: Reliable automation of the labor-intensive manual task of scoring animal sleep can facilitate the analysis of long-term sleep studies. In recent years, deep-learning-based systems, which learn optimal features from the data, increased scoring accuracies for the classical sleep stages of Wake, REM, and Non-REM. Meanwhile, it has been recognized that the statistics of transitional stages such as pre-REM, found between Non-REM and REM, may hold additional insight into the physiology of sleep and are now under viv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
(80 reference statements)
0
22
0
Order By: Relevance
“…TS is visually distinguishable from REM sleep due to the irregular shape of the continuous oscillation that also has a higher frequency than REM theta. It is challenging for an automatic algorithm to distinguish TS from REM due to the brief duration of TS (1.8% of the total sleep as reported by Grieger et al (2021)). However, the current consensus would be that TS would be part of NREM due to the spindle dominance. The detection of TS might alter our understanding of sleep in the rodents.…”
Section: Different Potential Light Nrem Sleep Stages In Rodentsmentioning
confidence: 99%
“…TS is visually distinguishable from REM sleep due to the irregular shape of the continuous oscillation that also has a higher frequency than REM theta. It is challenging for an automatic algorithm to distinguish TS from REM due to the brief duration of TS (1.8% of the total sleep as reported by Grieger et al (2021)). However, the current consensus would be that TS would be part of NREM due to the spindle dominance. The detection of TS might alter our understanding of sleep in the rodents.…”
Section: Different Potential Light Nrem Sleep Stages In Rodentsmentioning
confidence: 99%
“…We present the successful creation of a machine-learning-based classifier for the automated, accurate, and rapid scoring of sleep-wake states, seizures, and post-ictal states in mice with epilepsy. While previously reported classifiers effectively classified sleep in various populations of mice (Exarchos et al, 2020;Grieger et al, 2021;Lampert et al, 2015;Yamabe et al, 2019), none have demonstrated scoring proficiency in any rodent models of epilepsy. To our knowledge, our classifier is the first to achieve this goal.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, NREMS can be further divided into 3 stages, N1 to N3, ranging from the lightest sleep in N1 to the deepest sleep in N3. Human-like sleep stages have been revealed in mice in a few studies [16,17], but whether these stages have a physiological relevance remains to be explored. NREMS in mice, equivalent to human deep NREMS, is also termed as slow-wave sleep (SWS), with high-amplitude, lowfrequency oscillations as the dominant spectral power state.…”
Section: Nrem and Rem Sleepmentioning
confidence: 99%